Modelling Debris-Covered Glacier Ablation Using the Simultaneous Heat and Water Transport Model. Part 1: Model Development and Application to North Changri Nup - Winter-Billington, Alex; Dadić, Ruzica; Moore, R. D.; Flerchinger, Gerald; Wagnon, Patrick; Banerjee, Argha (Frontiers in Earth Science, 2022)
Modelling ablation of glacier ice under a layer of mineral debris is increasingly important, as the extent of supraglacial debris is expanding with glacier recession worldwide. Physically based models have been developed, but the uncertainty in predictions is not yet well constrained. A new one-dimensional model of debris-covered ice ablation that is based on the Simultaneous Heat and Water transfer model (SHAW) is introduced here. SHAW-Glacier is a physically complete, vertically integrated, fully coupled water and energy balance model, which includes the advection of heat by rainwater and lateral flow. In this study, SHAW-Glacier was applied to North Changri Nup, a high elevation alpine glacier in the monsoon-dominated Central Himalaya. Simulations were compared with observations of annual ablation, debris temperature profiles and snow depth at points within a 1 km$^2$ area, with debris ranging from 0.03 to 0.41 m thickness. Prediction uncertainty was estimated in a Monte Carlo analysis. SHAW-Glacier simulated the characteristic pattern of decreasing ablation with increasing debris thickness. However, the observations of ablation did not follow the characteristic pattern; annual ablation was highest where the debris was thickest. Recursive partitioning revealed sensitivity to the rain/snow threshold temperature. Photographs showed patches of snow persisting through the ablation season, and the glaciological observations were consistent with different ablation periods due to uneven persistence of snow patches. The analyses indicate patchy snow cover in the ablation season could represent an unquantified source of uncertainty in predictions of annual sub-debris ablation.